Spolia w budowlach konstantyńskich. Dekadencja, innowacja czy kontynuacja tradycji? - Anna Głowa (Vox Patrum, 2015)
“Spolia” is a term applied to earlier architectural elements re-used in new buildings. This practice was born in 3rd century and became very common in the times of Constantine. For a long time spolia were perceived as a sign of decline in late antique art. Nowadays interpretations of spolia alternate between the “pragmatic”, the “aesthetic” and the “ideological”. The aim of this article is to investigate these theories in context of changing tradition in ancient art, and try to see spolia as the reflection of the tension between “Past” and “Present” in the times of transformation of the Roman world.